Hot, cold, heavy, light 100 art writings, 1988-2018 - Schjeldahl, Peter 1942-2022 (Abrams Press, 2019)
'Hot Cold Heavy Light' collects 100 writings--some long, some short--that taken together form a group portrait of many of the world's most significant and interesting artists. From Pablo Picasso to Cindy Sherman, Old Masters to contemporary masters, paintings to comix, and saints to charlatans, Schjeldahl ranges widely through the diverse and confusing art world, an expert guide to a dazzling scene. No other writer enhances the reader's experience of art in precise, jargon-free prose as Schjeldahl does. His reviews are more essay than criticism, and he offers engaging and informative accounts of artists and their work. For more than three decades, he has written about art with Emersonian openness and clarity. A fresh perspective, an unexpected connection, a lucid gloss on a big idea awaits the reader on every page of this big, absorbing, buzzing book
Keywords: Schjeldahl, Peter -- 1942-2022; Geschichte 1988-2018; Kunstkritik; Aufsatzsammlung